2017
DOI: 10.19045/bspab.2016.50167
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of hexaploid wheat cultivars to drought stress

Abstract: Wheat is the most important cereal crop; it is staple diet for more than one third of the world population. Wheat production is influenced by several harsh environmental stresses that adversely affect its growth, metabolism and yield. Among them, Drought stress is the main factor limiting the productivity of wheat crop worldwide. Plants experience drought stress either when the water supply to roots becomes difficult or when the transpiration rate becomes very high. These two conditions often coincide under ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…Maximum SSC increase under severe stressed conditions (25 % FC) was observed in Mahmoudi, Swabaa Aljia and Jneh khotiffa with a sugar content increase about 15-fold [ see Supporting Information—Table S1 ] . These results were in accordance with Chaudhari et al . (2017) who observed that the soluble carbohydrate concentration in well-watered wheat plants was lower than that of stressed plants.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Maximum SSC increase under severe stressed conditions (25 % FC) was observed in Mahmoudi, Swabaa Aljia and Jneh khotiffa with a sugar content increase about 15-fold [ see Supporting Information—Table S1 ] . These results were in accordance with Chaudhari et al . (2017) who observed that the soluble carbohydrate concentration in well-watered wheat plants was lower than that of stressed plants.…”
Section: Resultssupporting
confidence: 93%
“…Our data showed that electrolyte leakage progressively amplified with increasing drought severity. These results are in agreement with a set of previous studies ( Chaudhari et al ., 2017 ). Similar to our results, Hairat and Khurana (2015) and Pour-Aboughadareh et al .…”
Section: Discussionsupporting
confidence: 94%
“…The decreased values of Canopy temperature depression (CTD) under open conditions might be due to higher rate of transpiration than shaded conditions that leads to water deficit and cause warmer canopy in open conditions. Similar results were also observed by Roohi et al, 2015 andChaudhari et al, 2017 Other physiological parameters such as photosynthetic rate, stomatal conductance and transpiration rate, decreased significantly in shaded conditions as compared to open conditions. In both environments, high CTD values were found in the intercropped condition.…”
Section: Canopy Temperature Differences In Shaded and Non-shaded Envi...supporting
confidence: 89%
“…Similarity index value for all the twenty genotypes ranged from 0.087 to 0.537 and two most closely related and diverse genotype in the twenty wheat genotypes have been observed in the present investigation (Table 4). [9] and Choudhary et al (2017) [6] ; which were in the range of 0.43 to 0.86 in wheat. Cluster analysis of twenty wheat genotypes revealed that all the used genotypes grouped into two major clusters namely A and B.…”
Section: Genetic Similarity and Cluster Analysis Of Different Wheat Genotypesmentioning
confidence: 97%